Epigenetic and breast cancer therapy: Promising diagnostic and therapeutic applications - Gulab Sher; Nadia Aziz Salman; Abdul Quaiyoom Khan; Kirti S. Prabhu; Afsheen Raza; Michał Kuliński; Said Dermime; Mohammad Haris; Kulsoom Junejo; Shahab Uddin (2020)
The global burden of breast cancer (BC) is increasing significantly. This trend is caused by several factors such as late diagnosis, limited treatment options for certain BC subtypes, drug resistance which all lead to poor clinical outcomes. Recent research has reported the role of epigenetic alterations in the mechanism of BC pathogenesis and its hallmarks include drug resistance and stemness features. The understanding of these modifications and their significance in the management of BC carcinogenesis is challenging and requires further attention. Nevertheless, it promises to provide novel insight needed for utilizing these alterations as potential diagnostic, prognostic markers, predict treatment efficacy, as well as therapeutic agents. This highlights the importance of continuing research development to further advance the existing knowledge on epigenetics and BC carcinogenesis to overcome the current challenges. Hence, this review aims to shed light and discuss the current state of epigenetics research in the diagnosis and management of BC.